MULTICOMPONENT SPECTROPHOTOMETRIC METHOD FOR SIMULTANEOUS ANALYSIS OF DELAPRIL AND INDAPAMIDE IN TABLETS - Vitor Todeschini; Regiane Leite; Maximiliano Sangoi; Paulo Oliveira; Thiago Barth (Drug Analytical Research, 2017)
A multicomponent ultraviolet (UV) spectrophotometric method was developed and validated for simultaneous determination of delapril (DEL) and indapamide (IND) in tablets employing the partial least squares regression (PLSR) approach. The PLSR method was developed by a multilevel factorial design using 25 synthetic mixtures of drugs and a significant predict model (p < 0.05) were obtained at 225 nm for DEL (r2 = 0.9992) and 243 nm for IND (r2 = 0.9997). Validation parameters such as the specificity, linearity, precision, accuracy and robustness were evaluated in accordance with the ICH requirements, giving satisfactory results within the acceptable range. The proposed PLSR method was successfully applied for simultaneous determination of DEL and IND in fixed dose combinations and can be used as simple alternative to separation techniques.